Identification of segments of European banks with a latent class frontier model - Carlos Pestana Barros; Guglielmo Maria Caporale; Luis A. Gil-Alana (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper analyses technical efficiency of European banks over the period 1996-2003 with unbalanced panel data techniques. A latent class frontier model is used which allows the identification of different segments in the production frontier. We find that there are three statistically significant segments in the sample. Therefore, we conclude that no common banking policy can be effective for all the banks included in the sample, and that banking policies by segments are required instead.
Keywords: C23; G21; 330; Bank; Marktsegmentierung; Technische Effizienz; Bankenpolitik; EU-Staaten